Seismicity Analysis of Earthquake in Bengkulu Using Gutenberg-Richter and Omori laws - Fiska Tobamba; Icha Untari Meidji; Harsano Jayadi (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2026)
Bengkulu Province is one of the regions in Indonesia with high seismic aktivity because it lies within the Sumatra tectonic plate zone and is crossed by the Sumatra Fault system. This tectonic setting makes Bengkulu highly vulnerable to Earthquake. This study analyzes the seismic characteristics of Bengkulu Using the Gutenberg-Richter law and examines the aftershock pattern following the major earthquake of june 4, 2000, based on the Omori-Utsu law. The data were obtained from the USGS earthquake catalog, consisting of earthquake records from 2015-2025 and afthershock data for 30 days after the mainshock. The Gutenberg-Richter Analysis evaluates the relationship between log10N and moment magnitude (Mw) to determine the a and b values. Meanwhile, Omori-Utsu Analysis examines the relationship between log10 n(t) and log10 (t+c) to obtain the parameters p and k. The result show that Bengkulu's seismicity is dominated by small to moderate earthquakes with relatively low b-values, indicating high tectonic stress conditions. The aftershock Analysis produced a p-value of 1.4822 with an R² value of 0.7767, showing rapid aftershock decay consistent with the Omori-Utsu law. These findings confirm Bengkulu has a high seismic Hazard level, emphasizing the need for continuous mitigation and preparedness efforts.